Una larga amistad. Correspondencia entre san Josemaría Escrivá de Balaguer y Mons. Manuel Fernández Conde (1942-1970) / A Lifelong Friendship. Postal Correspondence between St. Josemaría Escrivá and Msgr. Manuel Fernández Conde (1942-1970) - Francesc Castells i Puig (Studia et Documenta)
Since they first met in 1942, Josemaría Escrivá and Manuel Fernández Conde, who was Bishop of Cordoba (1959-1970), enjoyed a warm friendship. This friendship was reflected by an uninterrupted exchange of letters, especially on the occasion of birthdays, Saint’s days and other anniversaries. The correspondence between the two is detailed in this article.